2011
DOI: 10.1016/s0968-8080(11)37556-8
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity among immigrant women in the Netherlands: patients' perspectives

Abstract: This 2006 study investigated ethnicity-related factors contributing to sub-standard maternity care and the effects on severe maternal morbidity among immigrant women in the Netherlands. In-depth interviews were carried out with 40 immigrant and 10 native Dutch women. The immigrant women reported that health care providers often paid insufficient attention to their pregnancy-related complaints, especially in cases of pre-eclampsia. They also reported delays in receiving information about diagnosis and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 5 publications
1
62
0
1
Order By: Relevance
“…Ten studies examined empirical relationships between assessments of patients' HL and patients' understanding of information [9,14,15,17,19,23,33,35,50,51]. Across these studies, patients' understanding was variously defined and measured by researchers and the findings were also variable.…”
Section: Findings Relevant To the Information Exchange Stage Of The Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies examined empirical relationships between assessments of patients' HL and patients' understanding of information [9,14,15,17,19,23,33,35,50,51]. Across these studies, patients' understanding was variously defined and measured by researchers and the findings were also variable.…”
Section: Findings Relevant To the Information Exchange Stage Of The Tmentioning
confidence: 99%
“…First, the PDA(s) used in these studies were not developed to reflect the needs of patients with diverse levels of HL. Second, level of education was used in one study as an indicator of HL despite the fact that: (1) the relationship between HL and level education has been disputed in the literature, and (2) three studies included in this review reported a lack of correlation, or congruence, between level of education and level of HL 15 [18,34,51]. Third, in four studies, the care or treatment preferences of patients were elicited using PDAs that reflected a medical condition that most, if not all, patients in the study population did not have at the time of the study [38,39,40,41].…”
Section: Findings Relevant To the Deciding On The Treatment To Implemmentioning
confidence: 99%
“…More specifically, evidence suggests that immigrant status is associated with health adverse working conditions [1] [2]. With respect to health opportunities, several studies find poor health literacy, poor access to health services or poor utilization of health services among immigrants as compared to natives [3]- [7]. Evidence of unfavourable health behaviour of immigrants, such as lack of physical activity and unhealthy dietary habits and resulting risk factors such as overweight and obesity [8]- [12], has also been documented.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,16 Moreover, the women are able to provide information after the event, including the difficulties they faced in reaching timely obstetric treatment, 18 information that families of women who died may not be able to provide. 15,18,44 Indeed, some authors suggest that information on maternal near-miss events could be key for improving quality of care. 19,25 The high number of women arriving in poor clinical condition at referral facilities 19,34 may be considered as an indicator of the effectiveness of emergency referrals, while the number of near-misses may be an indicator of the performance of obstetric services.…”
mentioning
confidence: 99%